The Makna Rindu Rumah Pada Mahasiswa Perantauan: Makna Rindu Rumah Pada Mahasiswa Perantauan - Ahmad Ridha M ridha; Monica Angelina; Miftahul Jannah (PSYCHONESIA: JOURNAL OF PSYCHOLOGY, 2025)
The aim of this research is 3, namely identifying the reasons for students to travel, knowing the meaning of being away from home and how they overcome it. This study uses a qualitative method with a descriptive phenomenological approach. The results of this study show that the reason they migrate is to be more successful and independent, then also far from home is interpreted as a condition of homesickness which often causes negative emotions to disrupt daily activities. The way they deal with it is to let the feeling disappear over time and also social support.